EasyCoding - methodology to support programming learning - Almeida, Marcela Viana Pereira de (2020)
Knowing that the programming curricular units in the first year of engineering courses have a high failure rate and, assuming that this failure is due, in large part, to the lack of motivation and the lack of autonomy of the student to program in context outside the classroom, a methodology based on activity guides using attractive web platforms is proposed. The proposed methodology aims to facilitate both the planning of activities by the teachers and the autonomy and motivation by students. In order to receive a first feedback about this work, the methodology is being used by programming professors from Polytechnic Institute of Bragança, but in the near future it will be also evaluated by professors from the Federal Center of Technological Education of Minas Gerais and from the Federal Technological University of Paraná, both from Brazil. Following this work, a system is being developed that allows the automatic construction of guides based on exercises available from the web and systems that facilitate the collection of solutions and analysis of results.